Moment redistribution in continuous reinforced concrete beams: Experimental study and analytical investigation - Aydogan, Mehmet Safa; Aydemir, Cem; Arslan, Guray (ELSEVIER SCIENCE INC, 2024)
This paper presents the results of experimental and analytical studies carried out on continuous reinforced concrete (RC) beams to determine moment redistribution in statically indeterminate RC structures. For this purpose, continuous RC beams were produced with varying tensile reinforcement ratio at the intermediate support, which are shown as the parameters that affect moment redistribution the most in the literature. One of the main goals of this study is to check if the formulations in the design code provisions and in the literature give a safe estimate, and in order to perform this check, a dataset consisting of the experimental results of 141 beams in the literature has been used for validation and the moment redistribution ratios of this dataset have been estimated with all these formulations. The obtained results have been compared using various statistical indices such as the mean value (MV), standard deviation (SD), coefficient of variation (COV), the root mean square error (RMSE), mean absolute percentage error (MAPE). In particular, the formulations in the literature that take into account many parameters affecting the moment redistribution have been found to give better results than the formulations in the design code provisions. The results of this study confirm that elastic moment redistribution, which occurs in the process from the moment when the concrete cracks until the tensile reinforcement yields and constitutes a significant part of the total moment redistribution, is also important. Moreover, the properties of continuous RC beams related to their general behaviors, such as load-displacement relationships, ductility and moment-curvature relationships have been also investigated in detail.
Keywords: Moment redistribution; Continuous beams; Plastic rotation capacity; Ductility; Curvature; STRENGTH; PERFORMANCE; CAPACITY; BEHAVIOR; COLUMNS; Engineering